Histochemical assessment on the cellular interplay of vascular endothelial cells and septoclasts during endochondral ossification in mice. (20th August 2020) - Tsuchiya, Erika; Hasegawa, Tomoka; Hongo, Hiromi; Yamamoto, Tomomaya; Abe, Miki; Yoshida, Taiji; Zhao, Shen; Tsuboi, Kanako; Udagawa, Nobuyuki; Henrique Luiz de Freitas, Paulo; Li, Minqi; Kitagawa, Yoshimasa; et al.
Abstract: This study was aimed to verify the cellular interplay between vascular endothelial cells and surrounding cells in the chondro-osseous junction of murine tibiae. Many CD31-positive endothelial cells accompanied with Dolichos Biflorus Agglutinin lectin-positive septoclasts invaded into the hypertrophic zone of the tibial epiphyseal cartilage. MMP9 immunoreactive cytoplasmic processes of vascular endothelial cells extended into the transverse partitions of cartilage columns. In contrast, septoclasts included several large lysosomes which indicate the incorporation of extracellular matrices despite no immunopositivity for F4/80—a hallmark of macrophage/monocyte lineage. In addition, septoclasts were observed in c-fos -/- mice but not in Rankl -/- mice. Unlike c-fos -/- mice, Rankl -/- mice showed markedly expanded hypertrophic zone and the irregular shape of the chondro-osseous junction. Immunoreactivity of platelet-derived growth factor-bb, which involved in angiogenic roles in the bone, was detected in not only osteoclasts but also septoclasts at the chondro-osseous junction. Therefore, septoclasts appear to assist the synchronous vascular invasion of endothelial cells at the chondro-osseous junction. Vascular endothelial cells adjacent to the chondro-osseous junction possess endomucin but not EphB4, whereas those slightly distant from the chondro-osseous junction were intensely positive for both endomucin and EphB4, while being accompanied with ephrinB2-positive osteoblasts. Taken together, it is likely that vascular endothelial cells adjacent to the chondro-osseous junction would interplay with septoclasts for synchronous invasion into the epiphyseal cartilage, while those slightly distant from the chondro-osseous junction would cooperate with osteoblastic activities presumably by mediating EphB4/ephrinB2. Mini-abstract: Our original article demonstrated that vascular endothelial cells adjacent to the chondro-osseous junction would interplay with septoclasts for synchronous invasion into the epiphyseal cartilage, while those slightly distant from the chondro-osseous junction would cooperate with osteoblastic activities presumably by mediating EphB4/ephrinB2. (A figure that best represents your paper is Fig. 5 c)